In vitro Anti-Hantavirus Activity of Protein Kinase Inhibitor 8G1 Targeting AKT/mTOR/eIF4E Signaling Pathway - Li, Zhoupeng; Wang, Fang; Ying, Qikang; Kong, Dehui; Zhang, Xiaoxiao; Dong, Yuhang; Liu, Yongsheng; Zhai, Dongsheng; Chen, Zhou; Jia, Min; Xue, Xiaoyan; Li, Mingkai; et al. (Frontiers in Microbiology, 2022)
Hantaan virus (HTNV) is the main cause of hemorrhagic fever with renal syndrome (HFRS) around the world, which results in profound morbidity and mortality. However, there are currently no FDA-approved therapeutics or vaccines against HFRS. To find new anti-HTNV drugs, the inhibitory activity of 901 small molecule kinase inhibitors against HTNV is analyzed. Among these compounds, compound 8G1 inhibits HTNV with a relatively high inhibition rate and lower toxicity. The viral titer and nucleocapsid protein of HTNV are reduced after compound 8G1 treatment in a dose-dependent manner at concentrations ranging from 1 to 20 μM. In addition, the administration of compound 8G1 at the early stage of HTNV infection can inhibit the replication of HTNV. The molecular docking result reveals that compound 8G1 forms interactions with the key amino acid residues of serine/threonine-protein kinase B (Akt), which is responsible for the observed affinity. Then, the mammalian target of rapamycin (mTOR) and eukaryotic translation initiation factor 4E (eIF4E) signaling pathways are inhibited. Our results may help to design novel targets for therapeutic intervention against HTNV infection and to understand the anti-HTNV mechanism of protein kinase inhibitors.